DETERMINATION OF THE MILK COW BARN YIELD VALUE - Ivanović, Sanjin (Economics of Agriculture, 2006)
The study stresses the importance of milk cow barns for the successful production of milk. The possibility of determining the economic efficiency of investments in the purchase of cow barn was shown by evaluating its yield value under the production conditions of the family farms included in the poll. Based on the results obtained the yield value of milk cow barns using both combined and barn system breeding was found to be greater than its purchase value, i.e. investments in the construction of barns were found justifiable from the economic standpoint. In addition, greater yield value was recorded under the conditions of combined breeding system in relation to the milk cow barn breeding system. The input-output price relationship was found to effect yield value of milk cow barns as well.